Ethanol and phencyclidine interact with respect to nucleus accumbens dopamine release: differential effects of administration order and pretreatment protocol - Pickering, Chris; Chau, Pei Pei; Soderpalm, Bo; Ericson, Mia (Frontiers in Behavioral Neuroscience, 2010)
Executive dysfunction is a common symptom among alcohol-dependent individuals. Phencyclidine (PCP) injection induces dysfunction in the prefrontal cortex of animals but little is known about how PCP affects the response to ethanol. Using the in vivo microdialysis technique in male Wistar rats, we investigated how systemic injection of 5 mg/kg PCP would affect the dopamine release induced by local infusion of 300 mM ethanol into the nucleus accumbens. PCP given 60 min before ethanol entirely blocked ethanol-induced dopamine release. However, when ethanol was administered 60 min before PCP, both drugs induced dopamine release and PCP's effect was potentiated by ethanol (180% increase vs 150%). To test the role of prefrontal cortex dysfunction in ethanol reinforcement, animals were pretreated for 5 days with 2.58 mg/kg PCP according to previously used ‘PFC hypofunction protocols’. This, however, did not change the relative response to PCP or ethanol compared to saline-treated controls. qPCR illustrated that this low PCP dose did not significantly change expression of glucose transporters Glut1 (SLC2A1) or Glut3 (SLC2A3), monocarboxylate transporter MCT2 (SLC16A7), glutamate transporters GLT-1 (SLC1A2) or GLAST (SLC1A3), the immediate early gene Arc (Arg3.1) or GABAergic neuron markers GAT-1 (SLC6A1) and parvalbumin. Therefore, we concluded that PCP at a dose of 2.58 mg/kg for 5 days did not induce hypofunction in Wistar rats. However, PCP and ethanol do have overlapping mechanisms of action and these drugs differentially affect mesolimbic dopaminergic transmission depending on the order of administration.